Dampak Pembuangan Limbah Domestik terhadap Pencemaran Air Tanah di Kabupaten Pidie Jaya - Muhammad Gufran; Mawardi Mawardi (Jurnal Serambi Engineering, 2019)
One parameter of water quality is bacteriological content. Among the factors causing increased bacteriological content in water (SGL) are domestic waste. This study aims to determine the quality of water (SGL) in Keude Lueng Putu Village biologically, knowing whether distance (SGL) from polluting sources meets the requirements or not, determining whether physical conditions and construction (SGL) meet the requirements or not, and identify user behavior (SGL). The population in this study was 121 units (SGL) and those taken into samples using the Simple Random Sample technique were 10% of the total (SGL), which was 12 (SGL). For the independent variable distance / location of pollutant sources with bacteriological quality of water with  indicators of Coliform levels, it shows that the farther the distance of the pollutant source the lower the Coliform  level (having a negative correlation). While the correlation between the distance / location of pollutant sources with E. coli levels is very weak (Pearson correlation value is very small (0.013) .Correlation test for the second independent variable shows that the physical condition (SGL) does not have a significant effect on Coliform levels (p value 0.558), while E. coli levels show a correlation between construction (SGL) and E. coli levels, although this relationship is very weak because the p value is 0.067. The third independent variable explains the behavior of the people which greatly influences Coliform levels in water (SGL ) indicated by (p value) is 0.001 (0.05).